The Influence of Marketing Mix on Brand Image, Motivation and Students Decision to Choose Graduate Studies of IPB University - Arifin, Zukhri Agusty Leo Syamsul; Sumarwan, Ujang; Najib, Mukhamad (Journal of Consumer Sciences, 2020)
Competition in the recruitment of graduate students is increasingly tight with the large number of tertiary institutions offering graduate education programs. Universities must develop more competitive marketing strategies to win the competition in the student recruitment market. This study aims to analyze the effect of the marketing mix on brand-image, motivation, and student decisions in choosing a graduate education at the Bogor Agricultural University (IPB) as the place to pursue graduate study. This study uses a causality approach with survey techniques to explain the causal relationship between marketing mix variables, brand image, motivation, and student decisions. The data of this study were collected using a questionnaire from 255 master program students of IPB. Structural Equation Modeling (SEM) is used to analyze the causal relationship between marketing mix with brand-image, motivation, and student decisions. The results showed that products, promotions, people, and physical evidence significantly influence brand-image. Product, place, process, people, physical evidence, and brand image have a significant influence on motivation. The product, promotion, process, people, brand image, and motivation influence the student’s decision. Policy-makers at IPB can consider the findings of this study, while developing a graduate education marketing plan, to increase the number of new students.